2019
DOI: 10.1038/s41598-019-45357-y
|View full text |Cite
|
Sign up to set email alerts
|

Supercontinuum generation by co-filamentation of two color femtosecond laser pulses

Abstract: In this paper, we experimentally investigate supercontinuum generation via collinear two-color filamentation in sapphire crystal, by launching two femtosecond pulses at fundamental (1030 nm) and second harmonic (515 nm) wavelengths from an amplified Yb:KGW laser. By changing the time delay between the incident pulses, we observe dramatic changes in the supercontinuum spectrum, transmitted energy, position of the nonlinear focus and intensity distribution along the filamentinduced luminescence traces. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…SC has a wide range of applications, such as time-resolved excitation and absorption spectroscopy [45], optical pulse compression [46] and the characterization of laser-induced structural transitions [47], etc. The SC generation induced by femtosecond laser in water has been extensively studied in the past few decades, both experimentally and theoretically [39,[48][49][50][51][52][53][54][55][56]. Quite a few approaches are used to study the property of the SC and to control the SC generation [39,[48][49][50][51][52][53][54][55][56].…”
Section: Femtosecond Laser Filamentation and Sc Generation In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…SC has a wide range of applications, such as time-resolved excitation and absorption spectroscopy [45], optical pulse compression [46] and the characterization of laser-induced structural transitions [47], etc. The SC generation induced by femtosecond laser in water has been extensively studied in the past few decades, both experimentally and theoretically [39,[48][49][50][51][52][53][54][55][56]. Quite a few approaches are used to study the property of the SC and to control the SC generation [39,[48][49][50][51][52][53][54][55][56].…”
Section: Femtosecond Laser Filamentation and Sc Generation In Watermentioning
confidence: 99%
“…The SC generation induced by femtosecond laser in water has been extensively studied in the past few decades, both experimentally and theoretically [39,[48][49][50][51][52][53][54][55][56]. Quite a few approaches are used to study the property of the SC and to control the SC generation [39,[48][49][50][51][52][53][54][55][56]. For example, the coherence of the SC can be studied by the interference method [39,52].…”
Section: Femtosecond Laser Filamentation and Sc Generation In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Furthermore, they obtained the SC generation from collinear two-color filamentation in sapphire crystal, and also found that the transition between SC generation and its extinction will occur in a narrow delay region. [15] However, the output energy of the spectral enhanced SC is still limited to the level of µJ. In this work, by using an MLA, a mJ level SC with a very broad spectral range is obtained from the dual-color femtosecond filament array in fused silica.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al found that doping water with silver-nanoparticles can enhance the nonlinear optical response of water, leading to broadening of SC spectra induced by femtosecond filament [34]. Besides, polychromatic field scheme is another effective method to enhance the SC emission [37,38], for example, Vengris et al used two femtosecond pulses at 1030 nm and 515 nm wavelengths to irradiate the sapphire crystal, and by changing the time delay between the two pulses, they observed dramatic changes in the SC spectrum [37]. In effect, the polychromatic field scheme essentially belongs to the first approach, i.e., changing the property of femtosecond laser pulses.…”
Section: Introductionmentioning
confidence: 99%